Neurotic Perfectionism and Its Correlation with Psychological Resilience among a Sample of University Students - Meiri, Elwaleed Abdalla Farih (Journal of Ecohumanism, 2024)
The purpose of this study was to examine college students by gender and major to determine if there is a correlation between neurotic perfectionism and psychological resilience. Both the comparative and correlational styles made use of the descriptive technique. Of the 270 students surveyed, 147 were male (54.4% of the total) and 123 were female (45.6% of the total), all hailing from the College of Social Sciences' Psychology Department. There was a standard deviation of 2.6 for the guys' average age and 19.8 for the females, while the average age was 19.9 for both sexes. Their results were analysed using the Neurotic Perfectionism Scale (Yamani, 2018) and the Connor Davidson Psychological Resilience Scale (Sing and Nan Yu, 2010). According to the research, total neurotic perfectionism is directly related to factors like low self-esteem, wanting approval, doubting talents, and hardiness. The results showed no statistically significant correlation between toughness, overly worrying about making mistakes, and performance dissatisfaction. A direct correlation between optimism and low self-esteem, seeking approval, and doubt in abilities was found to be statistically significant. On the other hand, no correlation was found between optimism and total neurotic perfectionism, dissatisfaction with performance, or excessive concern with mistakes. When it comes to seeking approval, doubting one's abilities, and low self-esteem, there is a direct and statistically significant relationship between multiple sources. On the other hand, when it comes to excessive concern with errors, dissatisfaction with performance, and total neurotic perfectionism, there is no such relationship. An individual's level of neurotic perfectionism is not significantly correlated with their level of purpose or goal, excessive worry about making mistakes, dissatisfaction with their performance, or low self-esteem, but these variables are directly and statistically related to low self-esteem. While the total degree of neurotic perfectionism is significantly correlated with low self-esteem, seeking approval, and doubting one's abilities, there is no statistically significant correlation between lack of purpose or goal, excessive concern with errors, and dissatisfaction with performance and total psychological flexibility. The study also discovered that when looking at university students by gender and speciality, there were no statistically significant variations in the levels of neurotic perfectionionism and psychological flexibility. A number of recommendations were also reached by the study. One of them was to put more emphasis on university activities that foster psychological flexibility among students. Another was to increase university guidance services' ability to identify and help students with neurotic perfectionism.